Analisis peran zakat, infaq, shadaqoh dan wakaf di lembaga Dompet Dhuafa Jawa Timur sebagai upaya pengentasan kemiskinan di masyarakat - Muawanah; Fauziah, Nur Dinah; Demila; Akub Hambali Adi Zamick (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2023)
Purpose – This research was conducted because poverty and income inequality are still one of the problems that are often faced by the Indonesian people. Where poperty in question is one of the problems of the Indonesian nation which is very important, especially when there is a sharing of condominiums such as the global crisis which mainly affects food and an energy crisis. One of the things wer can see is the bgigh price of oil which will have an impact on poperty, especially in Indonesian. The formulation of the problem in this study is how the role of zakat, infaq and sadakah as a solution in alleviating poverty. The purpose of this study is that we can find out how the role of zakat, infaq and sadakah in alleviating poverty Method – The type of research that the author uses is descriptive qualitative. While data collection from this research is by way of observation and interviews Results – The results of this study indicate that the existence of zakat, infaq and sadakah can be used as a solution in alleviating poverty and income inequality, it can be seen that the existence of productive zakat programs can help zakat recipients in improving their economy. Limitations – this research has limitations in terms of the number of research informants, further research can expand information from various regions who receive zakat, infaq and hadaqah through dhuafa wallets. Practical Implications – this research is a recommendation for government policy to develop programs through social institutions and zakat institutions in order to reduce poverty.